RF MEMS based tunable bandpass filter using QMSIW resonator - Ur Rehman, M.Z. (National Institute of Optoelectronics, 2015)
A tunable bandpass filter based on a technique that utilizes quarter mode substrate integrated waveguide (SIW) is presented. This concept reduces the circuit foot print of SIW to a quarter of its size, along with miniaturization good performance and high quality factor is maintained by the structure. The design concept for single-pole resonator structure is presented; and by coupling the resonators a two-pole substrate integrated waveguide bandpass filter is achieved for the centre frequency of 5.9 GHz. Packaged RF MEMS switches are utilized to achieve tuning of 0.45 GHz for two frequency states of 6.0 and 6.45 GHz. The total size of the circuit is 32.4mm x 9.7mm x 0.787mm (LxWxH). Â© 2015, National Institute of Optoelectronics. All right reserved.